Nietzsche and the Critique of Revolution - Fontana, Antonio (Cambridge Scholars Publisher, 2019)
Revisiting over fifty years of post-structuralist, post-modernist, and Existentialist readings of Nietzsche, this study offers an incisive, scholarly deconstruction and critique of apolitical and individualist readings and interpretations of Nietzsche's philosophical corpus. Specifically, it views the German thinker as partaking of a larger intellectual tradition: the 19th century Western European reactionary, conservative, and counter-revolutionary tradition. The work combines genealogical and historical investigation with analysis of Nietzsche's life-long philosophical and ideological strugg.